Need help answering!!!

Howdoyoumath

New member
Joined
Jul 5, 2019
Messages
3
Given that f(x)=(x−3)^2 and g(x)=7−2x find

(a) (f+g)(3)=

(b) (f−g)(3)=

(c) (fg)(3)=

(d) (f/g)(3)=

Thanks
 

Otis

Senior Member
Joined
Apr 22, 2015
Messages
1,651
Need help answering!!! …
Hello. What kind of help do you need? That is, where did you get stuck?

Are you able to calculate the value of f(3) and the value of g(3) separately? If so, then add those two numbers (for part a). If you don't understand the symbols f(3) and g(3) -- or how to find their values -- please let us know.

(f+g)(3) means f(3) + g(3)

Likewise, (f−g)(3) means f(3) - g(3)

(fg)(3) = f(3) ∙ g(3)

(f/g)(3) = f(3) / g(3)

If you've started, please show the work you've tried so far.

PS: Check out the Read Before Posting notice, too. Thanks!

😎
 

Jomo

Elite Member
Joined
Dec 30, 2014
Messages
3,658
Given that f(x)=(x−3)^2 and g(x)=7−2x find

(a) (f+g)(3)=

(b) (f−g)(3)=

(c) (fg)(3)=

(d) (f/g)(3)=

Thanks
f(x) says to subtract 3 from x and then square the result. So f(3) says to subtract 3 from 3 and then square the result.
g(x) says to subtract twice x from 7. So g(3) says to subtract twice 3 from 7, that is 7-6.
 

Howdoyoumath

New member
Joined
Jul 5, 2019
Messages
3
Hello. What kind of help do you need? That is, where did you get stuck?

Are you able to calculate the value of f(3) and the value of g(3) separately? If so, then add those two numbers (for part a). If you don't understand the symbols f(3) and g(3) -- or how to find their values -- please let us know.

(f+g)(3) means f(3) + g(3)

Likewise, (f−g)(3) means f(3) - g(3)

(fg)(3) = f(3) ∙ g(3)

(f/g)(3) = f(3) / g(3)

If you've started, please show the work you've tried so far.

PS: Check out the Read Before Posting notice, too. Thanks!

😎
I have absolutely no idea about how i would start to answer this question. I'm guessing I need to graph the f(x)=(x−3)^2 and g(x)=7−2x into my calculator to determine the x values for each. For f(x)=(x−3)^2 the x value would be f(3)=(3−3)^2. Which doesn't make any sense because that would make it 0. Now if 0 is the correct answer do I plug that 0 for f into the given solutions like
(a) (f+g)(3)=

(b) (f−g)(3)=

(c) (fg)(3)=

(d) (f/g)(3)= ???
If so I think i have an idea on how to finish the problem.
 

pka

Elite Member
Joined
Jan 29, 2005
Messages
8,331
Suppose that \(\displaystyle f~\&~g\) are real valued functions with the same domain. Then
\(\displaystyle (f\pm g)(x)=f(x)\pm g(x)\)
\(\displaystyle \dfrac{f}{g}(x)=\dfrac{f(x)}{g(x)}\)
JUST FOLLOW THE PATTERN
 

Harry_the_cat

Senior Member
Joined
Mar 16, 2016
Messages
1,393
Given that f(x)=(x−3)^2 and g(x)=7−2x find

(a) (f+g)(3)=

(b) (f−g)(3)=

(c) (fg)(3)=

(d) (f/g)(3)=

Thanks
From post #4 it is clear that you don't understand function notation.
If \(\displaystyle f(x) = (x - 3)^2 \) then

\(\displaystyle f(1) = (1 - 3)^2 = (-2)^2 = 4 \)
\(\displaystyle f(2) = (2 - 3)^2 = (-1)^2 = 1 \)

So.… \(\displaystyle f(3) = ...….\)

In \(\displaystyle f(x) = (x-3)^2\), "f" is the name of the function (subtract 3 and then square) and x is the variable used in the function. x can take any value and f(x) is calculated accordingly.
\(\displaystyle g(x)=7 - 2x\) is a different function (double the number and then subtract from 7) and so has a different name "g".
So \(\displaystyle g(1) = 7 - 2*1 = 5\) etc.

Now what is f(3) and g(3)? (No graphing is needed)

You have been told above that (f+g)(x) = f(x) + g(x), so (f+g)(3) = f(3) + g(3) = ...... + ...... = ..........

Now do a similar thing with the other 3 questions.
 

Harry_the_cat

Senior Member
Joined
Mar 16, 2016
Messages
1,393
I have absolutely no idea about how i would start to answer this question. I'm guessing I need to graph the f(x)=(x−3)^2 and g(x)=7−2x into my calculator to determine the x values for each. For f(x)=(x−3)^2 the x value would be f(3)=(3−3)^2. Which doesn't make any sense because that would make it 0. Yes it is 0 ...why doesn't that make any sense? 0 is a number just like any other number
Now if 0 is the correct answer do I plug that 0 for f into the given solutions like You don't plug 0 for f, you plug 0 for f(3) because f(3) =0
(a) (f+g)(3)= f(3) + g(3) = 0 + ……. you finish it now

(b) (f−g)(3)=

(c) (fg)(3)=

(d) (f/g)(3)= ???
If so I think i have an idea on how to finish the problem.
See red above
Please post your answers and we will see if you understand.
 

Jomo

Elite Member
Joined
Dec 30, 2014
Messages
3,658
You need to know how to calculate the functions f and g in words. I stated the rules above in my previous post. Read it, think about, read it again repeat until you understand it.
 

HallsofIvy

Elite Member
Joined
Jan 27, 2012
Messages
5,046
For f(x)=(x−3)^2 the x value would be f(3)=(3−3)^2. Which doesn't make any sense because that would make it 0. Now if 0 is the correct answer do I plug that 0 for f into the given solutions
Yes, f(3)= 0. Why would that not make any sense? Surely you have seen many functions that have a value for some x? Yes, you "plug" that 0 into the given formulas. What did you get for g(3)?

(Your grammar is a little odd. It is not the "x value" that would be 0. The f value is 0 when the x value is 3. And you do not "plug that 0 for f into the given solutions" because there are NO "given solutions! You plug f(3)= 0 into the given formulas in order to get your solutions.)
 

Jomo

Elite Member
Joined
Dec 30, 2014
Messages
3,658
f(x)=(x−3)^2 and g(x)=7−2x
(f+g)(3) = f(3) + g(3) = [(3-3)^2] + [7-2*3] = [0] + [1] = 1
Now please do the rest
 
Top